Peran Pustakawan dalam Pengembangan Literasi Informasi di Perpustakaan Universitas Muhammadiyah Makassar: Indonesia - Ardiansyah, Fatri; Harianto,; Nasrullah, (Literatify : Trends in Library Developments, 2023)
Abstract This study exmines the role of librarians in developing information literacy in the library of the Muhammadiyah University of Makassar. The background in this research is based on the current situation where university libraries rarely teach informtion literacy to users. As for the main problem in this research is “the role of librarians in developing information literacy in the library of the University of Muhammadiyah Makassar”. From the subject matter above the researcher divided into 2 problems, namely: first how the role of librarians in developing information literacy in the library of the University of Muhammadiyah Makassar. And the second is the development of the information literacy in the library of the University of Muhammadiyah Makassar. This type of research is a qualitative descriptive study and a systematic managerial approach, where data is collected by using observation, interviews and documentation as well as using data management and analysis techniques which are carried out through four stage, namely data collection, data reduction, data presentation and taking conclusions. The role of librarians in developing information literacy is quite good, seeing librarians have carried out their functions as educators in educating librarians in literacy and managing information needed by the librarians. As an adminisrator, providing good services, in this case the provision of digital services, journals and a convenient place for the running of information literacy programs. As a supervisor, supervises and provides guidance to user. Whereas in the development of information literacy, each skill has gone well looking at the contribution of librarians in educating and applying skills in information literacy, starting from identifying information needs, tracking management tools, publicizing and using technology. As an implication, it is expected that a new breakthrough in the development of informtion literacy is needed to make this information literacy as a basic course, librarians must also be more creative in educating librarians and librarian also need to improve their competence. Keywords: information literacy.college’s library, librarian